1992
DOI: 10.1111/j.1365-2141.1992.tb08206.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐radioactive in situ hybridization for the detection and monitoring of trisomy 12 in B‐cell chronic lymphocytic leukaemia

Abstract: Non-radioactive in situ hybridization (NISH) with a chromosome 12-specific alpha satellite probe was performed on 20 patients with chronic lymphocytic leukaemia (CLL) with normal karyotype (15 cases) or with inadequate mitotic yield (5 cases) from mitogen-stimulated cultures. All patients had over 70% lymphocytes coexpressing the CD5/CD23 antigens. While less than 1% interphase nuclei showed three fluorescent spots in 16/20 patients, evidence of trisomy 12 in 15-25% interphase cells was detected in four patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…This anomaly was present in 5.13% of the cells, affecting only a subpopulation of B lymphocytes. Other studies have also reported on this abnormality presenting in only a proportion of cells from a malignant clone analyzed by FISH [21, 22, 23, 24], suggesting that trisomy is a late event in the pathogenesis of B-CLL, developing in an already established malignant B-cell clone.…”
Section: Discussionmentioning
confidence: 99%
“…This anomaly was present in 5.13% of the cells, affecting only a subpopulation of B lymphocytes. Other studies have also reported on this abnormality presenting in only a proportion of cells from a malignant clone analyzed by FISH [21, 22, 23, 24], suggesting that trisomy is a late event in the pathogenesis of B-CLL, developing in an already established malignant B-cell clone.…”
Section: Discussionmentioning
confidence: 99%
“…Trisomy 12 was the most common abnormality observed cytogenetically with an incidence of 8-20% of all cases Escudier et al, 1993;Que et al, 1993;Athanasiadou et al, 2006), but by FISH it is the second most common abnormality and has been observed in 7-35% of the cases (Anastasi et al, 1992;Cuneo et al, 1992;Escudier et al, 1993;Que et al, 1993;Matutes et al, 1996;Aoun et al, 2004;Goorha et al, 2004;Gozzetti et al, 2004;Glassman and Hayes, 2005;Sindelarova et al, 2005;Reddy, 2006). Trisomy 12 is strongly associated with atypical lymphocyte morphology, atypical marker expression, advanced stage of the disease and resistance to chemotherapy (Cuneo et al, 1992;Coignet et al, 1993;Escudier et al, 1993;Que et al, 1993).…”
Section: Trisomy 12mentioning
confidence: 99%
“…Trisomy 12 is strongly associated with atypical lymphocyte morphology, atypical marker expression, advanced stage of the disease and resistance to chemotherapy (Cuneo et al, 1992;Coignet et al, 1993;Escudier et al, 1993;Que et al, 1993). Expression of FMC7, CD38, CD20 and surface immunoglobulin light chain was significantly higher (Finn et al, 1996;Matutes et al, 1996;Ghia et al, 2003;Athanasiadou et al, 2006;Reddy, 2006).…”
Section: Trisomy 12mentioning
confidence: 99%
“…17,21 Therapy for CLL is unclear, with evidence that karyotypic abnormalities, particularly trisomy 12, may be a marker for resistance to conventional chemotherapy. 15 Fluorescence in situ hybridization (FISH) in interphase cytogenetics is becoming an increasingly performed method due to the difficulty of obtaining adequate cells in metaphase cytogenetics and is well documented in the detection of chromosomal abnormalities in various leukemias. 3 Detection of trisomy 12 by FISH has been performed on material from bone marrow, peripheral blood and lymph nodes 2,4,5,7,10,[12][13][14]17,18,[23][24][25][26][27][28]31 and has been found to be superior to that with conventional cytogenetics 2,12,13,16,17,24,25,27 or polymerase chain reaction.…”
Section: Objective: To Evaluate Fluorescence In Situ Hybridization (Fmentioning
confidence: 99%
“…The slides were removed and either placed in 95% ethanol or spray fixed and allowed to dry for [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] minutes. The slides were placed in tap water for 10 minutes and transferred to 95% ethanol for 15 minutes.…”
Section: Objective: To Evaluate Fluorescence In Situ Hybridization (Fmentioning
confidence: 99%